2010
DOI: 10.1111/j.1365-2664.2010.01929.x
|View full text |Cite
|
Sign up to set email alerts
|

Translating research into action; bumblebee conservation as a case study

Abstract: First paragraph: Bumblebees belong to the genus Bombus, which comprises about 250 species, largely confined to the temperate Northern Hemisphere. They are wholly dependent on flowers for their energetic and developmental requirements. Most are social species, with nest sizes varying from 50 to 400 workers. As such, they have attracted considerable attention regarding their role as pollinators. There is a growing body of evidence that bumblebees have declined in Europe, North America and Asia in recent decades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…Thus, of all remaining fragments of Vaccinium uliginosum on the Plateau des Tailles, the smaller populations probably did not offer enough resources to support large numbers of bumble bees. This underpins the notion that bumble bees are especially prone to habitat fragmentation [47]. In spring, V. uliginosum is probably a crucial floral resource in the area, providing important nectar and pollen supplies.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, of all remaining fragments of Vaccinium uliginosum on the Plateau des Tailles, the smaller populations probably did not offer enough resources to support large numbers of bumble bees. This underpins the notion that bumble bees are especially prone to habitat fragmentation [47]. In spring, V. uliginosum is probably a crucial floral resource in the area, providing important nectar and pollen supplies.…”
Section: Discussionmentioning
confidence: 65%
“…Such knowledge is fundamental in restored sites to evaluate conservation efforts [62]. Our results illustrate that V. uliginosum provides important resources for bumble bee species that are suspected to be in decline [47]. The plant species itself might not be at immediate risk of extinction.…”
Section: Resultsmentioning
confidence: 81%
“…Goulson et al . ). In contrast, we found that only one respondent (DOC employee) had never read an academic paper about hihi.…”
Section: Recovery Groups As a Conduit For Evidence‐based Conservationmentioning
confidence: 97%
“…Finally, in a twist on a statement made in an earlier practitioner's perspective (Goulson et al . ), we asked whether ‘publishing a scientific paper, no matter how good the science may be, does not in itself improve the fortunes of hihi’. The response was as the following: eight (47%) agreed, six (35%) disagreed and two were undecided.…”
Section: Recovery Groups As a Conduit For Evidence‐based Conservationmentioning
confidence: 99%
“…This is certainly not what we want, but we do welcome examples of best practice that may not have made it into the wider academic literature. The first Practitioner's Perspective appears in this issue (Goulson et al 2011) and illustrates the viewpoint of the Bumblebee Conservation Trust, although the lead author is a senior academic at Stirling University, UK. Hopefully, in addition to highlighting how science informs the conservation of bumblebees it will challenge readers to consider what more needs to be done.…”
mentioning
confidence: 99%